Adiponectin, markers of subclinical inflammation and nerve conduction in individuals with recently diagnosed type 1 and type 2 diabetes. Issue 4 (April 2016) - Schamarek, Imke; Herder, Christian; Nowotny, Bettina; Carstensen-Kirberg, Maren; Straßburger, Klaus; Nowotny, Peter; Strom, Alexander; Püttgen, Sonja; Müssig, Karsten; Szendroedi, Julia; Roden, Michael; Ziegler, Dan; et al.
Abstract : Objective: Subclinical inflammation has been implicated in the development of diabetic sensorimotor polyneuropathy (DSPN), but studies using electrophysiological assessment as outcomes are scarce. Therefore, we aimed to investigate associations of biomarkers reflecting different aspects of subclinical inflammation with motor and sensory nerve conduction velocity (NCV) in individuals with diabetes. Design and methods: Motor and sensory NCV was assessed in individuals with recently diagnosed type 2 ( n =352) or type 1 diabetes ( n =161) from the baseline cohort of the observational German Diabetes Study. NCV sum scores were calculated for median, ulnar and peroneal motor as well as median, ulnar and sural sensory nerves. Associations between inflammation-related biomarkers, DSPN and NCV sum scores were estimated using multiple regression models. Results: In type 2 diabetes, high serum interleukin (IL)-6 was associated with the presence of DSPN and reduced motor NCV. Moreover, higher levels of high-molecular weight (HMW) adiponectin, total adiponectin and their ratio were associated with prevalent DSPN and both diminished motor and sensory NCV, whereas no consistent associations were observed for C-reactive protein, IL18, soluble intercellular adhesion molecule-1 and E-selectin. In type 1 diabetes, only HMW and total adiponectin showed positive associations with motor NCV. Conclusions: Our results point to a link between IL6 and both DSPN and slowed motor NCV in recently diagnosed type 2 diabetes. The reverse associations between adiponectin and NCV in type 1 and type 2 diabetes are intriguing, and further studies should explore whether they may reflect differences in the pathogenesis of DSPN in both diabetes types.